Safe School Study, 1976-1977 ([Verlag nicht ermittelbar], 1984)
This data collection contains information obtained from a total of 31,373 students, 23,895 teachers, and 15,894 principals in the United States in 1976-1977 in the Safe School Study, mandated by the United States Congress under Public Law 93-380 (Section 825). The legislation was in response to growing public concern regarding incidents of violence and vandalism occurring in the nation's schools. The objectives of this study were to determine the frequency and seriousness of crime in elementary and secondary schools in the United States, the number and location of schools affected by crime, the cost of replacement or repair of objects damaged by school crime, and possible methods of prevention. The legislation specified that the study was to be conducted by the National Institute of Education (NIE). The NIE designed the study in three phases, and data collection was carried out by the Research Triangle Institute, with computer work supervised by Sheldon Laube of C.M. Leinwand Associates. The primary data for the study were collected in two concurrent sample surveys: Phase I and Phase II. Phase I, a mail survey, asked more than 4,000 elementary and secondary school principals to report in detail on the incidence of illegal or disruptive activities in their schools. Nine one-month reporting periods between February 1976 and January 1977, excluding summer months, were assigned to participating schools on a random basis. Parts 2 and 11 contain data gathered from school principals in this phase. In Phase II, field representatives conducted on-site and follow-up surveys of junior and senior high school students and teachers in public secondary schools. They were asked to report any experiences they might have had as victims of violence or theft in the reporting month. In addition, they provided information about themselves, their schools, and their communities. Also, the principals in this sample were asked to keep a record of incidents during the reporting month, including robberies, attacks, and thefts. They also supplied information about their schools' characteristics and crime prevention methods. Parts 7, 16, 19, 24, 29, 30, 35, 39, 43, and 47 contain the data gathered in this phase. Part 18 contains the combined data gathered in the Principal questionnaires, utilizing both Phase I and Phase II samples. Part 51 is a file created to supply community information about each Phase II school. Most of its information was extracted from the 1970 Census, but it also includes weather and unemployment data. Phase III involved a more intensive qualitative study of 10 schools, most which had had a history of problems with crime and violence, but which had improved dramatically in a short time. Some crimes explored were vandalism, theft, personal violence, and verbal abuse. The place of occurrence and characteristics of each offender were also examined. The 10 case studies created as a result of Phase III can be read in the primary codebook for this data collection: United States Department of Health, Education, and Welfare. National Institute of Education. VIOLENT SCHOOLS -- SAFE SCHOOLS: THE SAFE SCHOOL STUDY REPORT TO THE CONGRESS, VOLUME 1. Washington, DC: United States Department of Health, Education, and Welfare, 1978.